Tau and Aβ42 in lavage fluid of pneumonia patients are associated with end-organ dysfunction: A prospective exploratory study. - Phoibe Renema; Jean-Francois Pittet; Angela P Brandon; Sixto M Leal; Steven Gu; Grace Promer; Andrew Hackney; Phillip Braswell; Andrew Pickering; Grace Rafield; Sarah Voth; Ron Balczon; et al. (PLoS ONE)
Background Bacterial pneumonia and sepsis are both common causes of end-organ dysfunction, especially in immunocompromised and critically ill patients. Pre-clinical data demonstrate that bacterial pneumonia and sepsis elicit the production of cytotoxic tau and amyloids from pulmonary endothelial cells, which cause lung and brain injury in naïve animal subjects, independent of the primary infection. The contribution of infection-elicited cytotoxic tau and amyloids to end-organ dysfunction has not been examined in the clinical setting. We hypothesized that cytotoxic tau and amyloids are present in the bronchoalveolar lavage fluid of critically ill patients with bacterial pneumonia and that these tau/amyloids are associated with end-organ dysfunction. Methods Bacterial culture-positive and culture-negative mechanically ventilated patients were recruited into a prospective, exploratory observational study. Levels of tau and Aβ42 in, and cytotoxicity of, the bronchoalveolar lavage fluid were measured. Cytotoxic tau and amyloid concentrations were examined in comparison with patient clinical characteristics, including measures of end-organ dysfunction. Results Tau and Aβ42 were increased in culture-positive patients (n = 49) compared to culture-negative patients (n = 50), independent of the causative bacterial organism. The mean age of patients was 52.1 ± 16.72 years old in the culture-positive group and 52.78 ± 18.18 years old in the culture-negative group. Males comprised 65.3% of the culture-positive group and 56% of the culture-negative group. Caucasian culture-positive patients had increased tau, boiled tau, and Aβ42 compared to both Caucasian and minority culture-negative patients. The increase in cytotoxins was most evident in males of all ages, and their presence was associated with end-organ dysfunction. Conclusions Bacterial infection promotes the generation of cytotoxic tau and Aβ42 within the lung, and these cytotoxins contribute to end-organ dysfunction among critically ill patients. This work illuminates an unappreciated mechanism of injury in critical illness.